Sex selection through traditional drugs in rural north India - Bandyopadhyay S; Singh A (Wolters Kluwer Medknow Publications, 2007)
Background : Repidly declining sex ratio has highlighted a strong son preference among many societies various methods are employed by people to get a son. Objective: To determine the use pattern of sex selection drugs (SSDs) in rural North India. Methods: An integrated qualitative and quantitative study was conducted in rural North India. A rapid population and hospital based survey of women in their early reproductive life was done in the study area to enlist the respondents. Few SSD samples were collected and analyzed. Results: SSDs were freely available from grocers, chemist shops and specific people in villages. These contained Shivalingi (Bryonia Laciniosa) and Majuphal (Gtuercus infectoria). SSD use rate was 46% and 30% in community based and hospital based studies respectively. Use rate was significantly higher in women who did not have any son. Of the SSD samples and two individual ingredients analyzed by thin layer chromatography, 3 contained testosterone and one progesterone; one ingredient contained testosterone and the other natural steroids. Conclusion: Use of SSDs seems to be very common in North India. Implication of presence of steroids in SSDs needs further evaluation.